MATHEMATICAL MODEL OF CONSUMER INTEREST IN VIRAL FOOD - Naomi Binroos Siregar, Cyntya
The presence of social media has led to several topics going viral, one of which is the widespread sharing of information about food. Numerous groups, particularly those identified as food influencers, share reviews and recommendations that pique the interest of social media users to purchase viral foods. Business enthusiasts and owners of small and medium-sized enterprises (SMEs) also capitalize on the viral momentum to attract consumer interest. This Final Dissertation models the dynamics of consumer interest in viral foods circulating in the market by modifying the predator-prey model and examining the intrinsic factors and the roles of restaurants in relation to viral foods, as well as the social influence that impacts purchase decisions. The virality of the examined foods is represented using the Richard curve. The unit volume hypothesis is employed to illustrate the level of viral food circulation in the market and the level of consumer interest in viral foods. The dynamic behavior of the constructed system is examined, with compartments representing the level of circulation of viral foods in the market and the level of consumer interest. The presence of equilibrium conditions and their stability are studied using Eigen-values analysis and Jacobi matrices. Numeric analysis using logistic functions and the Richard curve are observed to illustrate the outcomes of the constructed model. From the numerical analysis, it is inferred that foods that rapidly reach their viral peak (fad) tend to have larger scaling parameters compared to foods that gradually attain peak virality but then integrate into society (trend). To understand consumer interest trends, a survey is conducted to identify factors influencing consumer interest in viral foods. By adjusting parameter values based on survey results, it is also found that the more a factor is perceived to influence respondents’ purchase decisions, the longer consumers remain interested in viral foods. In other words, the most influential factors for a viral food to remain discussed and become a trend are taste and price.